الإسهامات و الأدوار الجديدة للجامعة في ظل اقتصاد المعرفة –الواقع و التحديات - بواب, رضوان (University of Eloued جامعة الوادي, 2019)
يبرز دور الجامعات من خلال مساهمتها الفعالة في عملية وصقل معارف الأجيال و في بناء مجتمع المعرفة وإخراج كفاءات تلاءم و تخدم سوق العمل ، و بصفتها مؤسسة علمية لنشر المعرفة والحقائق حتى خارج مجالها قادرة على إنتاج المعرفة و تسويقها ،حيث تصبح مرتكزا أساسيا في بناء اقتصاديات الدول وتعزيز التنمية الاقتصادية المستدامة المرجوة . ومع التطور الحاصل في جميع المجالات خاصة ثورة المعلومات و انفجارها،وانتشار تكنولوجيا المعلومات والاتصالات،و أصبح من الضروري الاعتماد على المعرفة كآلية لتغيير و تطوير مناحي الحياة الاجتماعية وخاصة الاقتصادية، و نجاح أي اقتصاد ليتأتى إلا من خلال إعطاء دور أكبر للمعرفة وإنتاجها داخل مؤسسات التعليم العالي القادرة على حمل هذا الإرث و تفعيله لدرجة الاعتماد شبه الكلي على المعرفة في تحقيق التنمية الاقتصادية الكفيلة بمواصلة مسيرة الحياة. الكلمات المفتاحية:الجامعة،التعليم الجامعي ،المعرفة ،مجتمع المعرفة ،اقتصاد المعرفة. Abstract:- It highlights the role of universities through their effective contribution to the process and refinement of the knowledge of the generations, the building of the knowledge society, the creation of competencies that suit and serve the labor market, and as a scientific institution to disseminate knowledge and facts, even outside of its domain, capable of producing and marketing knowledge. And promote the desired sustainable economic development. With the development in all areas, especially information revolution and explosion, and the spread of information and communication technology, it has become necessary to rely on knowledge as a mechanism to change and develop aspects of social life, especially economic, and the success of any economy to come only by giving a greater role of knowledge and production within educational institutions Which is capable of carrying this legacy and activating it to the degree of almost total dependence on knowledge in achieving economic development to ensure the continuity of life. Keywords: university, university education, knowledge, knowledge society, knowledge economy. الكلمات المفتاحية
Keywords: الجامعة-التعليم الجامعي-المعرفة -مجتمع المعرفة-اقتصاد المعرفة